2009
DOI: 10.1007/s12011-009-8487-6
|View full text |Cite
|
Sign up to set email alerts
|

Serum Trace Element Levels in Febrile Convulsion

Abstract: Febrile convulsion is the most common disorder in childhood with good prognosis. There are different hypotheses about neurotransmitters and trace element changes in biological fluids which can have a role in pathogenesis of febrile convulsion. In this study, serum selenium, zinc, and copper were measured by atomic absorption spectrometry in the children with febrile convulsion (n = 30) and in the control group (n = 30). The age and sex of the subjects were registered. Selenium and zinc were found to be signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
49
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 18 publications
11
49
1
Order By: Relevance
“…The changes in bio-elements in FS explained the respond of the metabolism. Amiri et al found signifi cantly low levels of Se and Zn in patients with FS (21).…”
Section: Discussionmentioning
confidence: 98%
“…The changes in bio-elements in FS explained the respond of the metabolism. Amiri et al found signifi cantly low levels of Se and Zn in patients with FS (21).…”
Section: Discussionmentioning
confidence: 98%
“…The findings are consistent with some previous studies. 5,[9][10][11][12][13]19,20 Hypozincemia in present study was found to be more prevalent in children with simple febrile seizures compared to the control group. However, no classical clinical manifestations of hypozincemia like diarrhoea, impaired appetite, decreased growth velocity, acroorificial skin lesions, delayed wound healing, dysguesia and hypoguesia were present in these patients, demonstrating purely biochemical hypozincemia.…”
Section: Discussionmentioning
confidence: 64%
“…4,5 Zinc has an important role in various processes at the cellular level. It is involved in cellular growth and differentiation, is an important cofactor in various enzymatic activities taking place in different organs, proteins and cellular metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…3 Many studies have shown an association between low serum selenium levels and febrile seizures equally. [3][4][5] Some studies have shown no association. 6 Hence our study is an attempt to evaluate the association between the serum selenium level and febrile seizures.…”
Section: Introductionmentioning
confidence: 99%